Análisis e implementación de un secadero para base de cultivo en cajas petri para la inoculación de tricodermas en la producción de abonos orgánicos - Enríquez Rivadeneira, Santiago Fernando (2016)
The project is essentially based on the implementation of a dryer cultivation base, for inoculating trichoderma, increasing production efficiently where the final product is used as a plant nutrient or creating organic fertilizers being therefore one great application within the agricultural industry in the country. The work of titling developed, partly with Chapter 1 where the investigation of the generalities of the trichoderma, types and classification of dryers, air properties and elements that make up the design of the dryer as centrifugal fan, electric motor, drying chamber is performed, frame among others. In chapter 2 the analysis of three alternatives where implementation is done dryers arises, obtaining the most suitable option dryer cultivation base system with electrical resistance and centrifugal fan. The design and respective calculations of the elements involved in implementing the dryer is presented in Chapter 3, which is referenced theoretical data and calculation equations, in order to present results to ensure proper operation and production desired at a set time. Additional in Chapter 4, referred to the costs involved in implementing the dryer, thus determining the initial cost, final and return on investment. It also results that support the implementation of the selected dryer was achieved consequently improves crop production base for inoculation of trichoderma effectively and efficiently